Adaptation of Technology in Open Distance Learning: A Case Study of AIOU - Asia Zulfqar, Syed Nasir Hussain (PJDOL, 2019)
The purpose of this study was to explore how AIOU is adapting technological innovations in their distance education programs and to what extent instructional design has been aligned with the technologybased online learning. A qualitative research design was adopted to collect data from key IT experts working behind the provision of online learning and the tutors who are using the online learning platform. A semi-structured interview protocol was designed to interview the participants. An interpretive data analysis approach was adopted to reach at the conclusions. The majority of the respondents acknowledged the need of the adaptation of technology in distance education and discussed different opportunities offered through LMS and other online resources.